Probation of the offender with high functioning autistic traits and comorbidity. A case study. (13th April 2021) - Riolo, A.; Keller, R.; Battaglia, R.; Albert, U.
Abstract : Introduction: When the Criminal Court Judge applies probation, the offender is entrusted to social assistants for the necessary observation, treatment and support. This case study examines the probation of a young man with high-functioning autistic traits, personality disorder and legal/illegal substance abuse. This young man, who arrived only in adulthood to a diagnosis of autistic traits, is aware only that is non-neurotypical. He does not recognize that he needs treatment for personality disorder, alcohol, substance and drug abuse. He faces a sentence of more than three years in prison but the Judge suspends the criminal trial. Objectives: Clarify the relationship between high functioning autistic traits, comorbidity with personality disorder and drugs/substance abuse, and crimes committed; also describe the orientation of the Judge and what difficulties arise during the probation. Methods: Examination of the criminal file and medical documents of the offender, known by social and health services. Results: The offender correlates the crimes and its frailty with autism and not with antisocial behaviours to gain economic benefits from drug dealing. Conclusions: The deficit in the social communication and lack of empathy for child victimes, for example, limits the effectiveness of probation. The probation, for a young with high-functioning autistic traits and comorbidity, does not seem to give satisfactory results in terms of rehabilitation and social integration, nor does it produce the extinction of crime.